Profil Sendetary Life Style Pada Remaja Umur 15-17 Tahun ( Study Di Kabupaten Lamongan ): Profile of Sendetary Life Style for Adolescents Age 15 – 17 ( Study in Lamongan Regency ) - wahyubunga (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2022)
Physical activity is divided into three categories of low, medium and high. Low physical activity poses a major health risk. Low physical activity triggers sedentary habits resulting in obesity. Obesity is a condition where a person experiences excess fat accumulation in the body. The purpose of this study was to describe the sedentary lifestyle profile of adolescents aged 15-17 years (study in Lamongan Regency). Survey research was carried out in this study and used a quantitative descriptive approach with 176 students at SMK N 1 Lamongan as subjects. Retrieval of data using the International Physical Activity Questionnaire (IPAQ) analysis using descriptive analysis using the SPSS application. The results of the study showed that adolescents aged 15-17 years in Lamongan had a low sedentary time of 72.2%, a high of 27.8%. For an overview of physical activity, moderate results were obtained with the highest percentage of 69.5%. Followed by high activity 27.8% and 9.7% low. The description for the body mass index is that the highest percentage is 64.8% normal. Followed by lean with a percentage of 20.5%, obesity 9.1% and obesity 5.7%. The conclusion from this study is that the Covid 19 pandemic did not make youth aged 15-17 years in Lamongan spend their time practicing a sedentary lifestyle. Disturbances during the Covid 19 pandemic, teenagers in Lamongan continued to carry out physical activities that were in the moderate category. Keywords: covid, sedentary lifestyle, physical activity.